Técnica de fisioterapia respiratória expiração lenta e prolongada (ELPr): alterações funcionais pulmonares em lactentes sibilantes - Lanza, Fernanda de Cordoba [UNIFESP] (2009)
Introduction: Chest physiotherapy techniques may assist in the removal of airways secretions. Infants suffering from pulmonary infections can be benefit from these techniques. A limited number of studies has already evaluated the efficacy of these techniques in children. Lung function measurements could improve the evaluation of such techniques. Prolonged slow expiration technique (PSET) is a passive physiotherapy technique used for the removal of expectorated secretions in infants. Although widely employed, some doubts remain regarding its effectiveness. Objective: To evaluate changes in respiratory parameters during and after the performance of PSET in infants, including expiratory reserve volume (ERV), passive respiratory mechanics and the presence of sighs. Methods: Infants attending the Infant Pulmonary Function Testing Laboratory (UNIFESP) for lung function testing participated in the study. Infants under two years of age and with history of recurrent wheezing were chosen for the study. Infants suffering from gastric reflux disease or recovering from abdominal or thoracic surgery were excluded. Infants were sedated with chloral hydrate (60 – 80 mg/Kg, orally). Measurements were performed during sleep, after sedation, with a mask sealed adapted to the child’s face and connected to a pneumotachometer. Several parameters from normal breathing (peak expiratory flow [PEF], tidal volume [TV], respiratory rate [RR]) and from passive respiratory mechanics (compliance, resistance and time constant of respiratory system) were recorded before, during and after the PSET. Three thoracic compressions (PSET), executed to prolong the expiratory phase, were carried out: A, B and C. Increase in TV over 100% was considered sighs, before, during or immediately after the PSET. Raised volume rapid thoracic compression technique was performed at the end of the test to measure ERV. Results: 18 infants were evaluated. Their mean age was 32,3 ± 11,4 weeks and they had, on average, 4,8 ± 1,9 previous wheezing exacerbations. After PSET, significant changes were observed for TV (79,3 ± 15,6 ml vs 82,7 ± 17,2 ml; p = 0,009) and for RR (40,6 ± 6,9 bpm vs 38,8 ± 5,9 bpm; p = 0,042). PEF and passive respiratory mechanics parameters did not change significantly after the PSET. An expressive reduction in TV was measured during PSET compressions (82,3 ±16,5 ml vs 48,5 ± 10,8 ml; p < 0,001). Increased frequency of sighs was noted during and immediately after PSET (p = 0,035). Progressively exhalation of ERV was observed in each thoracic compression (32 ± 17,8% in A, 40,9 ± 23,9% in B, and 53 ± 19,6% in C; p = 0,035). Conclusions: We could document several PSET assumptions in wheezing infants, we observe an increase in TV and reduce in RR after application. It acts as a slow technique because there was no change in PEF. The TV was reduced during PSET. The technique facilitates the induction of sighs. There was a progressively reduces ERV and it is higher when more compressions were done.